2019
DOI: 10.1186/s12893-019-0495-7
|View full text |Cite
|
Sign up to set email alerts
|

New dedicated blunt straight needles and sutures for uterine compression sutures: a retrospective study and literature review

Abstract: BackgroundWe developed a dedicated blunt straight needle with No. 2 polydioxanone sutures (2-Monodiox®) for uterine compression sutures (UCSs) and aimed to assess the outcomes and complication rates of UCSs for postpartum hemorrhage by comparing with commercially available needle and suture types.MethodsA retrospective analysis was performed between January 2010 and February 2018. During the study period, two types of commercially available sutures and 2-Monodiox® were used. PubMed, MEDLINE, and Scopus databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…4 Treatment strategies include pharmacological measures (eg, oxytocin administration), intrauterine tamponade (eg, Bakri balloon or Sengstaken-Blakemore tube), uterine artery ligation, hysterectomy, uterine compression sutures, and uterine artery embolization (UAE). [5][6][7][8][9][10][11][12] A few publications have shown higher rates of preterm birth, fetal growth restriction (FGR), and placenta accreta spectrum (PAS) among women who became pregnant after UAE for PPH. However, these obstetric outcomes were not investigated with non-UAE cases in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…4 Treatment strategies include pharmacological measures (eg, oxytocin administration), intrauterine tamponade (eg, Bakri balloon or Sengstaken-Blakemore tube), uterine artery ligation, hysterectomy, uterine compression sutures, and uterine artery embolization (UAE). [5][6][7][8][9][10][11][12] A few publications have shown higher rates of preterm birth, fetal growth restriction (FGR), and placenta accreta spectrum (PAS) among women who became pregnant after UAE for PPH. However, these obstetric outcomes were not investigated with non-UAE cases in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…2 Polydioxanone (2-Monodiox), which is novel dedicated blunt straight needles. 4 The retrospective study was suggested that the uterine preservation rate was similar for 2-Monodiox with modified Hayman suture and No.1 poliglecaprone 25 sutures with B-Lynch suture without the occurrence of severe complications. 4 We modified both the needle type and the thread color.…”
Section: Discussionmentioning
confidence: 95%
“…4 The retrospective study was suggested that the uterine preservation rate was similar for 2-Monodiox with modified Hayman suture and No.1 poliglecaprone 25 sutures with B-Lynch suture without the occurrence of severe complications. 4 We modified both the needle type and the thread color. As a straight needle could penetrate the anteroposterior uterine wall, care was taken during the needle handling.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations